A re‐evaluation of management units based on gene flow of a rare waterbird in the Americas. (7th October 2020) - Shahrokhi, Golya; Rodriguez, David; Collins, Samantha; Kent, Gina; Meyer, Ken; Palacios, Eduardo; Green, Michael Clay
Abstract: The maintenance of gene flow in species that have experienced population contractions and are geographically fragmented is important to the maintenance of genetic variation and evolutionary potential; thus, gene flow is also important to conservation and management of these species. For example, the Reddish Egret ( Egretta rufescens ) has recovered after severe population reductions during the 19th and 20th centuries, but population numbers remain below historical levels. In this study, we characterized gene flow among management units of the Reddish Egret by using ten nuclear microsatellite markers and part of the mitochondrial (mtDNA) control region from 176 nestlings captured at eight localities in Mexico (Baja California, Chiapas, Tamaulipas, and Yucatan), the USA (Texas, Louisiana, and Florida), and the Bahamas. We found evidence of population structure and that males disperse more often and across longer distances compared with females, which is congruent with previous banding and telemetry data. The maternally inherited mtDNA and biparentally inherited microsatellite data supported slightly different MU models; however, when interpreted together, a four MU model that considered population structure and geographic proximity was most optimal. Namely, MU 1 (Baja California); MU 2 (Chiapas); MU 3 (Yucatan, Tamaulipas, Texas, and Louisiana); and MU 4 (Florida and the Bahamas). Regions outside our sampled localities (e.g., the Greater Antilles and South America) require additional sampling to fully understand gene flow and movement of individuals across the species' entire range. However, the four MUs we have defined group nesting localities into genetically similar subpopulations, which can guide future management plans. Abstract in Spanish is available with online material Resumen: El mantenimiento del flujo genético en especies geográficamente fragmentadas, y que han experimentado contracciones poblacionales es importante para el mantenimiento de la variación genética y el potencial evolutivo; así, el flujo de genes también es importante para la conservación y el manejo de estas especies. La garceta rojiza ( Egretta rufescens ) se ha recuperado después de severas reducciones poblacionales durante los siglos XIX y XX, pero la población permanece por debajo de los niveles históricos. En este estudio, caracterizamos el flujo genético entre las unidades de manejo (UM) de la garceta rojiza usando diez marcadores de microsatélites nucleares y parte de la región de control mitocondrial (ADNmt) de 176 polluelos capturados en ocho localidades de México (Baja California Sur, Chiapas, Tamaulipas y Yucatán), Estados Unidos (Texas, Louisiana y Florida) y Bahamas. Encontramos evidencia de estructura poblacional y de que los machos se dispersan con más frecuencia y en distancias más largas que las hembras, lo que es congruente con datos previos de aves marcadas y telemetría. El ADNmt heredado de la madre y los datos de microsatélites heredados biparentalmente apoyaron modelos de UM ligeramente diferentes; sin embargo, cuando se interpretaron juntos, un modelo de cuatro UM que consideró la estructura de la población y la proximidad geográfica fue el más óptimo. Es decir, UM 1 (Baja California); UM 2 (Chiapas); UM 3 (Yucatán, Tamaulipas, Texas y Luisiana); y UM 4 (Florida y Bahamas). Las regiones fuera de nuestras localidades muestreadas (por ejemplo, las Antillas Mayores y América del Sur) requieren un muestreo adicional para entender el flujo genético y el movimiento de los individuos en todo el intervalo de distribución de la especie. Sin embargo, las cuatro UM que hemos definido agrupan las localidades de anidación en subpoblaciones genéticamente similares, que pueden guiar los planes de manejo futuros.